IMPROVING THE QUALITY OF EDUCATION BY EFFECTIVE USE OF TECHNICAL TOOLS - Pardabayeva Rano Farkhod daughter (Scholars Digest Publishing, 2023)
In this article, the importance of using technological tools and materials to improve the quality of education in elementary grades, the good aspects of their effective use, and the changes in the teaching process of the student and teacher through technical tools are brought out.
Keywords: Technology, information, education, globalization, teacher, technical tools.